(untitled) (Archeomatica, 2016)
In the last years Bing Maps has been updated to offer new ways for tourism, through the integration of Yelp, Booking, Tripadvisor and Trivago, but it has abandoned the primary aim: a real alternative to Google Earth. Recently a new software suddenly apperead: Esri ArcGis Earth. This will replace definitively Google Earth. After the case study of Veio, Bing Maps returns and shows a hidden "Ostia”, revealing buried structures and building of not excavated areas (Regio III, Regio IV, Regio V and the Harbour of Trajan).